2005
DOI: 10.4049/jimmunol.175.9.5809
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Suppresses Osteoclastogenesis and Bone Destruction by Inducing IFN-β Production

Abstract: Osteoclasts are bone-resorptive multinucleated cells that are differentiated from hemopoietic cell lineages of monocyte/macrophages in the presence of receptor activator of NF-κB ligand (RANKL) and M-CSF. Downstream signaling molecules of the receptor of RANKL, RANK, modulate the differentiation and the activation of osteoclasts. We recently found that histone deacetylase inhibitors (HDIs), known as anticancer agents, selectively suppressed osteoclastogenesis in vitro. However, the molecular mechanism underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 53 publications
(63 reference statements)
4
90
1
1
Order By: Relevance
“…Earlier studies have shown that broadspectrum HDACi decrease survival and maturation of osteoclasts by inducing p21 expression without alterations to the p27 level, 23 blocking the RANKL signalling pathway or by increasing the mRNA level of IFN-b expression, an inhibitor of the osteoclastogenesis. 56 Furthermore, the HDACi, PDX101, in combination with bortezomib synergistically inhibits osteoclast formation in human BM cultures. The underlying mechanism of this synergism in vitro in osteoclast cells remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that broadspectrum HDACi decrease survival and maturation of osteoclasts by inducing p21 expression without alterations to the p27 level, 23 blocking the RANKL signalling pathway or by increasing the mRNA level of IFN-b expression, an inhibitor of the osteoclastogenesis. 56 Furthermore, the HDACi, PDX101, in combination with bortezomib synergistically inhibits osteoclast formation in human BM cultures. The underlying mechanism of this synergism in vitro in osteoclast cells remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] The continuous production of IFN-b by injection of IFN-b-expressing fibroblast or daily subcutaneous treatment with recombinant IFN-b inhibited inflammation as well as bone destruction in a system of collagen-induced arthritis in mice. 52,53 In addition, the expression of IFN-b was increased in synovial tissue of patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Briefly, 5-week-old female Lewis rats were intradermally injected at the base of the tail with complete adjuvant consisting of 25 mg/kg heat-killed M. butyricum (Difco Laboratories) suspended in mineral oil. In control experiments, rats were injected with mineral oil alone.…”
Section: Preparation Of Rat Primary Osteoblastsmentioning
confidence: 99%